POSSIBILITYIES OF PHYTOTHERAPY AT DIGESTIVE SYSTEM DISEASES - A. V. Kurkina; V. R. Galyamova; V. A. Kurkin; E. V. Avdeeva (Фармация и фармакология (Пятигорск))
In the present paper the modern approaches to the reasonable using of phytopharmaceuticals for diseases of gastrointestinal tract were discussed. Substantiates using groups of medicinal plants for the treatment of diseases of gastrointestinal tract based on important relationship «biologically active substance-pharmacological effect». According modern data of chemical composition and pharmacological activity in the attitude to this pathology the most important species of medicinal plants are considered. The importance of principle of phytotherapy’s safety as a main approach of evidential medicine was highlighted. This scientific paper will help experts to make an evidence-based decision of medicinal plants and phytopreparations based on them in clinical practice.